GENDER PHYSIOLOGICAL FEATURES OF STUDENTS DURING THE PROCESS OF EDUCATION (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This article looks through gender discrepancies in cognitive processes mainly attention, among first-year students. According to an experimental study using the "Landolt Rings" methodology, the indicators of concentration, distribution, and volume of attention were analyzed for both male and female students. The research findings show that in spite of some minor variations in average scores, the level of attention development in both groups is high. The article emphasizes the significance of considering gender-specific characteristics when structuring the educational process to achieve maximum learning efficiency.
Keywords: concentration distribution and volume